DESIGN AND DEVELOPMENT OF TWO ROW TRACTOR OPERATED POTATO COMBINE HARVESTER - Gulati, Sunil (Potato Journal, 2019)
Potato harvesting is one of the most important operations, which have to be performed precisely, to have good quality potatoes. A two- row tractors operated potato combine harvester having provision for side conveying of the harvested potatoes in the trolley, has been designed and developed. It consists of seven major units viz. main frame, digging system, elevator conveyor, side delivery / discharge conveyor, trash separation and soil sieving system, power transmission and transport system. The prototypes functions to dig out, separate dug tubers from soil mass, conveys, elevates and fill in a trolley. The effective field capacity of the potato combine was found as 0.26 ha/hr.